Kurdish Factor In Provision Of Regional Security In Middle East - Farkhod Karimov (International Journal of Advanced Science and Technology, 2020)
In the article, an attempt of studying of the role of the Kurdish problem in ensuring regional security and in relations between the countries of the Middle East and their participation in regional socio-political processes. Also, it has been studied the positions of the Middle East states on this issue and the influence of the external factor are considered. Main purpose of the article is clarifying Kurdish people in one whole and unique ethnicity as the largest nation where no its own country. Outcomes can be drawn as four different point of views on evaluation of the political situation in international collaboration. Conclusion considered that political threat and inequality still dominates in Middle East and only cooperation with international community can provide balance and peace in the region.